Analisis Perancangan Alat Pemetik Buah Mangga (LATIKMA) - Minaturrahim, Husain; Afief, Muhammad Rayhan; Firly, Teuku Muhammad; Maulana, Sofyan; Restianti, Vika; Parwati, Niken (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2022)
Product development is something that is needed by every existing company. At this time, almost all companies are competing to continue to develop their products to attract consumers to be able to run life easily and comfortably. In this study, we analyzed the design of the LATIKMA (Mango Fruit Picker) to make it easier for people to pick mangoes and have other goals so that the mangoes that were picked were not crushed. This study using 4 methods, namely RPW, MRPW, LCR, and J. Wagon. With a total time of 147 minutes and the total time of all work stations being the same for the RPW method, the number of stations is 10, the line efficiency is 74%, and the smoothing index is 22.56, then for the MRPW, the number of stations is 10, the line efficiency is 74%, and the smoothing index is 22.56, then for the J. Wagon the number of stations is 10, the line efficiency is 74%, and the smoothing index is 30.14, and for the LCR method, the number of stations is 9, the line efficiency is 82%, and the smoothing index is 13.22.Keywords - Product, OPC, Assembly Chart, Heuristic, Prototyp